Advancements and applications of space borne of remote sensing in climate change research: A scoping review - Ricky Anak Kemarau; Zaini Sakawi; Khairul Nizam Abdul Maulud; Wan Shafrina Wan Mohd Jaafar; Stanley Anak Suab; Oliver Valentine Eboy; Nik Norliati Fitri Md Nor; Zulfaqar Sa’adi (Elsevier B.V, 2025)
This scoping review explores the progress and applications of space-borne remote sensing within the realm of climate change research. It systematically compiles significant advancements in remote sensing technology, with a focus on its application for tracking diverse indicators of climate change. The review performs a thorough examination of various sensor types and technologies, evaluates the challenges and limitations encountered, and considers methods to overcome these obstacles. By adopting an integrated and multidisciplinary approach, the study connects the gap between technological progress and its policy implications, alongside mitigation and adaptation strategies. This offers a holistic view of the pivotal role of remote sensing in the study of climate change, providing valuable insights for researchers, policymakers, and practitioners alike.